2015
DOI: 10.1111/acel.12289
|View full text |Cite
|
Sign up to set email alerts
|

Stn1 is critical for telomere maintenance and long‐term viability of somatic human cells

Abstract: Disruption of telomere maintenance pathways leads to accelerated entry into cellular senescence, a stable proliferative arrest that promotes aging-associated disorders in some mammals. The budding yeast CST complex, comprising Cdc13, Stn1, and Ctc1, is critical for telomere replication, length regulation, and end protection. Although mammalian homologues of CST have been identified recently, their role and function for telomere maintenance in normal somatic human cells are still incompletely understood. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 42 publications
3
24
0
Order By: Relevance
“…Since ROS, generated through the TGF‐β1/Smad3/NOX4‐signaling pathway, caused telomere dysfunction and proliferative arrest of human somatic fibroblasts that lack detectable telomerase activity, but did not affect proliferation rates of fibroblasts expressing hTERT, our data suggest that opposing effects of TGF‐β1 on cell proliferation depend on the levels of telomerase activity in a cell. The insensitivity of hTERT‐expressing fibroblasts to TGF‐β1‐induced growth arrest and myofibroblast transdifferentiation likely is due to the ability to telomerase to suppress the formation of dysfunctional telomeres in cells encountering ROS‐induced telomeric replication stress, as demonstrated previously (Boccardi et al, 2015). As hTERT expression reduced formation of both telomeric and to some extent also nontelomeric DDR foci, it is also possible, however, that noncanonical functions of telomerase, such as its ability to reduce cellular ROS production (Saretzki, 2014), contribute to suppressing activation of a DDR and myofibroblast transdifferentiation of human fibroblasts.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Since ROS, generated through the TGF‐β1/Smad3/NOX4‐signaling pathway, caused telomere dysfunction and proliferative arrest of human somatic fibroblasts that lack detectable telomerase activity, but did not affect proliferation rates of fibroblasts expressing hTERT, our data suggest that opposing effects of TGF‐β1 on cell proliferation depend on the levels of telomerase activity in a cell. The insensitivity of hTERT‐expressing fibroblasts to TGF‐β1‐induced growth arrest and myofibroblast transdifferentiation likely is due to the ability to telomerase to suppress the formation of dysfunctional telomeres in cells encountering ROS‐induced telomeric replication stress, as demonstrated previously (Boccardi et al, 2015). As hTERT expression reduced formation of both telomeric and to some extent also nontelomeric DDR foci, it is also possible, however, that noncanonical functions of telomerase, such as its ability to reduce cellular ROS production (Saretzki, 2014), contribute to suppressing activation of a DDR and myofibroblast transdifferentiation of human fibroblasts.…”
Section: Discussionsupporting
confidence: 65%
“…Similarly, using human fibroblasts in which dysfunctional telomeres can be repaired using a doxycycline inducible hTERT expression system (Patel et al, 2016), we demonstrate that induction of hTERT expression in TGF‐β1 transdifferentiated myofibroblasts again reduced the levels of α‐SMA expressed in cells (Supporting Information Figure S3f). While the primary function of telomerase is to elongate telomeres and suppress formation of dysfunctional telomeres generated due to telomere shortening and ROS‐induced telomeric replication stress, (Boccardi et al, 2015; Patel et al, 2016), telomerase also possesses noncanonical functions that promote DNA repair and cell survival (Martinez & Blasco, 2011). To determine whether noncanonical functions of hTERT contribute to the suppression of myofibroblast transdifferentiation, we overexpressed in human BJ fibroblasts DN‐hTERT, a dominant defective mutant of hTERT that inactivates the catalytic activity of hTERT while leaving its noncanonical functions intact (Hahn et al, 1999).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the first reports on the effect of transcription on genetic stability in a eukaryotic system showed that HOT1, a segment of the ribosomal DNA locus that is actively transcribed by RNA polymerase I, could function as a cis-acting enhancer of recombination in S. cerevisiae [229]. A similar increase in recombination and spontaneous mutations was observed with high transcription levels by RNA Pol II [230,231]. Two different hypotheses explain the stimulation of spontaneous recombination by transcription: the first one centers around the increased accessibility of homologous recombination proteins to the DNA during transcription; the second hypothesis suggests that collisions between the transcription and replication machineries, the presence of stalled replication forks during transcription, or the formation of transcription-associated DNA:RNA hybrids (R-loops) can be significant sources of DNA damage and TAR ( Figure 8).…”
Section: Transcription-associated Mutagenesis and Recombinationmentioning
confidence: 85%
“…Because replication forks stall naturally at mammalian telomeres, an ATR-dependent fork restart mechanism is needed to complete DNA replication [227][228][229]. Knockdown of expression of CST components decreases bromodeoxyuridine incorporation at telomeres after release from hydroxyurea-induced replication fork arrest, and elicits telomere fragility [212,226,[230][231][232][233][234][235][236]. Several lines of evidence suggest that CST contributes to fork restart not only in telomeres but also genome-wide under conditions of replication stress [232,233,235,237].…”
Section: The Cst Complexmentioning
confidence: 99%